Relation between the morphometric parameters of Thymus and fetal weight. - Carmen Niurka Piña Loyola; Marta Rosa Gonzalez Debén; Alfredo Quiñones Ceballos (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: When we are born, thymus weighs about 10 or 13 g. This organ can develop as a result of the interaction among various factors that have been classified as physiological and pathological. Some studies to establish morphological patterns of this organ have reported dissimilar results. Objective: To determine morphometric parameters of thymus and it relation with fetus weight in Cienfuegos province between the years 2003-2008. Methods: A correlational, descriptive, observational study was carried out in the period between May, 2003 and May 2008. We took a sample of thymus of 147 cases of fetal death, out of a total of 151 cases, from the 17th gestational week to the end of the gestation period. Besides, we carried out measurements of this organ such as weight, height, width, thickness and volume whose variability was analyzed in relation with fetal weight. Results: There was correspondence between the gestational age and fetal weight. The morphometric parameter of thymus augmented in relation with fetal weight, being significant for fetal weights over 1500 g, where the morphologic variables of thymus reached values two fold those of the previous range. Conclusions: The more the fetus stays in the uterus the greater is its morphological and organic development, which is related with the inherent characteristics of intrauterine development for fetal period.